The Semeiosis of Poetic Metaphor - Haley, Michael Cabot (Indiana University Press, 1988)
How might an understanding of semeiosis enrich our understanding and appreciation of the literary work? Micael Cabot Haley investigates the creative working of metaphor from the perspective of the semeiotic theory of Charles Sanders Peirce. Haley bringes Peirce's sign theory, categories, philosophical realism, and objective idealism to bear upon metaphor, illustrating the role of figruative semeiosis as a creative principle of semantic growth in literature, language, and consciousness. The Peircean metaphor is shown to be a "metaicon," which appears in poetry as a perennially fresh srchetypal metaphor, generating a myriad of poetic diagrams and images. Peirce's central man-as-symbol metaphor is revealed as grounded in a symmetrical metaicon controlling and guiding abductive discovery of many kinds. Haley applies this Peircean scheme to actual literary uses of metaphor by such poets as William Shakespeare, John Keats, and T. S. Eliot, revealing in abundant detail just how Peircean conception works itself out in practice. Haley's clear-headed, perspicacious analysis takes a first step toward the founding of a Peircean semeiotic of figurative language.